Strategic Role of Self-Management Ability in Mitigating Work Stress and Enhancing Psychological Well-Being among Healthcare Professionals - Della Febiani Dwi Sumadi; Saida Zainurossalamia ZA (Manunggal Halim Jaya, 2026)
Psychological well-being is a vital indicator of quality of life for healthcare professionals navigating intense environments, yet the interplay of stress, motivation, and self-regulation remains underexplored in specialized medical settings. This study empirically investigates the partial effects of occupational stress, work motivation, and self-management ability on the psychological well-being of employees at the Eye Hospital of East Kalimantan Province. Employing an explanatory quantitative design, primary data were collected from 57 medical and nursing staff using purposive sampling and a Likert-scale questionnaire. The empirical data were then analyzed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). Contrary to conventional expectations, the findings reveal that neither occupational stress nor work motivation exhibits a significant partial effect on psychological well-being, indicating that employees rely on developed clinical resilience and require holistic organizational support rather than isolated motivational triggers. Conversely, self-management ability demonstrates a significant positive effect, acting as a crucial psychological buffer against clinical pressures. Theoretically, this research highlights self-regulation competence as a more dominant predictor of mental stability compared to motivation or the mere absence of stressors. Managerially, the findings suggest a paradigm shift for healthcare administrators, emphasizing the need to prioritize comprehensive work ecosystems and self-management capacity building to sustainably enhance human resource resilience.